2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--5559
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Model For Teaching Communication Skills In Engineering Curricula

Abstract: He obtained both his baccalaureate and master's degrees from LSU ME and his doctorate from Purdue University's School of Mechanical Engineering. He has been actively engaged in teaching, research and curricula development since joining the faculty in 1988.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A faculty survey we reported in 2009 and discuss later in this paper demonstrates how many of the reservations about this requirement were allayed. 7 Feedback and Revision Techniques. One of the challenging requirements of C-I courses in engineering is that students must receive feedback from the instructor on drafts of formal assignments.…”
Section: Communication Intensive (C-i) Coursesmentioning
confidence: 99%
“…A faculty survey we reported in 2009 and discuss later in this paper demonstrates how many of the reservations about this requirement were allayed. 7 Feedback and Revision Techniques. One of the challenging requirements of C-I courses in engineering is that students must receive feedback from the instructor on drafts of formal assignments.…”
Section: Communication Intensive (C-i) Coursesmentioning
confidence: 99%
“…2 Faculty assessment of C-I courses in 2008 showed that workload increased somewhat for both faculty and students in C-I courses; however, it was also acknowledged that students' knowledge of traditional course content was enhanced. 3 Another key element in the CxC program was the establishment of communication studios in the various colleges. The first of these, the Engineering Communication Studio (Studio), was opened in the fall of 2005.…”
Section: Introductionmentioning
confidence: 99%